124 IMPLICAŢII PEDAGOGICE ALE FUNCŢIONALISMULUI DURKHEIMIAN - USM ADMIN (Moldova State University, 2010)
Pedagogical work of Emil Durkheim is considered by some authors as "the legitimate daughter of his sociology" is still a valuable source of inspiration for theory and educational practice. Considered, rightly, the founding father of sociology Durkheim structured education in the context of his sociological work postulates a series of rules, in unequivocal terms, in the context of contemporary educational systems.